Hemolytic Disease of the Fetus and Newborn due to Intravenous Drug Use - Kara B. Markham; Scott R. Scrape; Mona Prasad; Karen Q. Rossi; Richard W. O'Shaughnessy (Thieme Medical Publishers, Inc., 2016)
Abstract Objectives The objective is to present a pregnancy complication associated with intravenous drug use, namely, that of red blood cell alloimmunization and hemolytic disease of the fetus and newborn. Methods An observational case series is presented including women with red blood cell alloimmunization most likely secondary to intravenous drug abuse Results Five pregnancies were identified that were complicated by red blood cell alloimmunization and significant hemolytic disease of the fetus and newborn, necessitating intrauterine transfusion, an indicated preterm birth, or neonatal therapy. Conclusions As opioid abuse continues to increase in the United States, clinicians should be aware of the potential for alloimmunization to red blood cell antibodies as yet another negative outcome from intravenous drug abuse.